If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = 7x + 9 Reorder the terms: -4 + 2x = 7x + 9 Reorder the terms: -4 + 2x = 9 + 7x Solving -4 + 2x = 9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -4 + 2x + -7x = 9 + 7x + -7x Combine like terms: 2x + -7x = -5x -4 + -5x = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 -4 + -5x = 9 + 0 -4 + -5x = 9 Add '4' to each side of the equation. -4 + 4 + -5x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 9 + 4 -5x = 9 + 4 Combine like terms: 9 + 4 = 13 -5x = 13 Divide each side by '-5'. x = -2.6 Simplifying x = -2.6
| 8a+6=4a+20 | | 91=x^2(91/x^2) | | 2x+5=x*5-4 | | -1-10h=-31 | | 0.5(x+2)=15 | | x/4=3/11 | | x^2(91/x^2) | | 2x-22=66 | | 6(4x-4)-5(x-2)= | | 40x^2-14x=0 | | 22-2x=66 | | 4(-4a-9b)= | | 1/3=5n-1/4 | | .14(300+x)+.06(y)=376 | | x*3-2=6+x | | x-7=-12x | | -5x^2-5x-10=0 | | c=15n+5 | | .7-4y=1.74 | | 3c=19+-2 | | 6x^3+37x^2-34x+7=0 | | 900=45m | | 8-2y=40 | | 27=-y/7 | | 2f-7=13 | | 1.6a+(-4)=.32 | | 0=(2x-3)(x+5) | | Z+11=25 | | Z+11=209 | | 11y=209 | | 2/5×3/9 | | 9x^2-72x-16y^2-32=16 |